1989
DOI: 10.1017/s0022112089002685
|View full text |Cite
|
Sign up to set email alerts
|

Slow spreading of a sheet of Bingham fluid on an inclined plane

Abstract: To study the dynamics of fluid mud with a high concentration of cohesive clay particles, we present a theory for a thin sheet of Bingham-plastic fluid flowing slowly on an inclined plane. The physics is discussed on the approximate basis of the lubrication theory. Because of the yield stress, the free surface need not be horizontal when the Bingham fluid is in static equilibrium, nor parallel to the plane bed when in steady flow. We then show that there is a variety of gravity currents that can advance at a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
167
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(178 citation statements)
references
References 11 publications
11
167
0
Order By: Relevance
“…While much of the earlier work has focused on time-dependent flows of viscous fluids over a rigid boundary [14][15][16][17], a growing attention has been paid to the corresponding problem with viscoplastic fluids from the theoretical point of view [18][19][20][21][22][23][24][25][26][27][28][29]. On rare occasions, exact or asymptotic analytical solutions to the governing equations can be worked out [10,21,[30][31][32][33][34], but most of the time, solutions must be computed numerically using flow-depth averaged equations of motion (the equivalent of the shallow-water equations in hydraulics) [35][36][37], nonlinear diffusion equations when inertial terms are negligible [19,21], or the full set of equations of motion (using a finite-element approach or smooth-particle-hydrodynamics techniques).…”
Section: Introductionmentioning
confidence: 99%
“…While much of the earlier work has focused on time-dependent flows of viscous fluids over a rigid boundary [14][15][16][17], a growing attention has been paid to the corresponding problem with viscoplastic fluids from the theoretical point of view [18][19][20][21][22][23][24][25][26][27][28][29]. On rare occasions, exact or asymptotic analytical solutions to the governing equations can be worked out [10,21,[30][31][32][33][34], but most of the time, solutions must be computed numerically using flow-depth averaged equations of motion (the equivalent of the shallow-water equations in hydraulics) [35][36][37], nonlinear diffusion equations when inertial terms are negligible [19,21], or the full set of equations of motion (using a finite-element approach or smooth-particle-hydrodynamics techniques).…”
Section: Introductionmentioning
confidence: 99%
“…Provided the yield stress is exceeded, then to leading order the down-slope velocity exhibits a shearing region close to the basal boundary, overridden by a plug-like region (see, for example [18]). At the yield surface between the two, the velocity field and shear stress are continuous.…”
Section: Formulationmentioning
confidence: 99%
“…Liu and Mei [18] studied the transient slump into a channel that has a pre-existing layer of fluid and they showed how the slump is progressively slowed and then finally arrested as the driving forces are no longer able to surmount the yield stress. Huang and Garcia [16] analysed the motion along an initially fluid-free channel: their calculations revealed that strong curvatures in the free surface are only found close to the propagating front and this permitted a simplified analysis of the motion in which the front was handled separately and matched to the interior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations